Method for preparing hard carbon microspheres by utilizing solvothermal catalytic crosslinking of coal pitch and application

The aromatic hydrocarbons in coal asphalt are initiated through a catalyst for cross-linking reaction, and the solvent thermal catalysis process is used to solve the problem that coal asphalt is difficult to maintain a stable hard carbon microsphere in the emulsion state in the medium and low softening point, and hard carbon microspheres with high specific capacity are prepared for the negative electrode of sodium ion battery.

CN119735199APending Publication Date: 2025-04-01UNIV OF JINAN

Patent Information

Application Number
CN202510231706.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The polymerization and crosslinking degree of coal asphalt in medium and low softening points is low, making it difficult to maintain a stable hard carbon microsphere morphology in the emulsion state.

Method used

The catalyst is used to induce the cross-linking reaction of other aromatic hydrocarbons in the raw coal asphalt to form large molecular weight planar aromatic molecules, and finally form hard carbon microspheres through a solvent thermal catalysis process.

Benefits of technology

Hard carbon microspheres with large carbon layer spacing and abundant defect positions were prepared, and have a high specific capacity when applied to the negative electrode of sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735199A_ABST
    Figure CN119735199A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a method for preparing hard carbon microspheres by utilizing solvothermal catalytic crosslinking of coal pitch and application. The preparation method of the hard carbon microspheres comprises the following steps: adding a catalyst into coal pitch, carrying out solvothermal pretreatment, and carbonizing to obtain the coal pitch-based hard carbon microspheres. The preparation method has the characteristics of simplicity, economy, environmental protection and the like. High-temperature and high-pressure conditions are provided by utilizing a solvothermal method, low-softening-point coal pitch is taken as a carbon source, large-molecular-weight planar aromatic hydrocarbon molecules are formed by utilizing a cross-linking reaction initiated by a catalyst, then the planar aromatic hydrocarbon molecules are coalesced through interaction of electron forces and separated out from a liquid-phase matrix, and finally balling is performed under the action of surface tension. A proton cocatalyst is selected as a solvent to provide a cation source to improve the catalytic activity of the catalyst, and finally the hard carbon microspheres with large carbon layer spacing and rich defect sites are prepared. The hard carbon microspheres can be used for preparing sodium ion batteries and have important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing hard carbon microspheres by utilizing solvent thermal catalytic cross-linking of coal tar pitch, and application of the hard carbon microspheres as negative electrode materials for sodium ion batteries. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, the rapid development of electronic devices and electric vehicles has further increased society's energy demand and put forward higher requirements for energy storage systems. Lithium-ion batteries are about to reach the limit of their energy density. Therefore, electrochemical energy storage systems with similar mechanisms to ion batteries and abundant sodium source reserves have become one of the most promising next-generation electrochemical energy storage systems.

[0004] Coal tar and other polycyclic aromatic hydrocarbons are good precursors of carbon materials because they have a high carbon yield under the induction of benzene rings. Coals of different coal ranks have different molecular structures and can effectively form various types of nanocarbon materials, such as carbon nanosheets, graphene oxide, carbon dots, hard carbon microspheres, etc. In particular, hard carbon microspheres are widely used in chemical catalysis, secondary batteries and supercapacitors because of their advantages such as good electrical and thermal conductivity, large specific surface area, high stacking density, excellent thermal stability and chemical stability. There are various methods for preparing hard carbon microspheres, generally including arc discharge method, chemical vapor deposition, template method, emulsification method, suspension method and solvent (water) thermal method. High softening point coal tar has been used as a precursor for preparing hard carbon microspheres because it has a high degree of crosslinking and is easy to form balls. However, the preparation process of high softening point coal tar is also relatively complicated, and the prepared coal tar balls also need to be oxidized and infusible before annealing. Compared with high softening point coal tar, medium and low softening point coal tar is a direct distillation product of coal tar, with simple preparation process and low cost. However, due to its low degree of polymerization and cross-linking, it is difficult to maintain a stable form in the emulsion state. Therefore, low softening point coal tar is used as a precursor in the preparation of hard carbon microspheres by emulsion method, but there is little research on it. Summary of the invention

[0005] Aiming at the key problem that the existing medium and low softening point coal tar pitch has low polymerization degree and crosslinking degree, and it is difficult to maintain a stable hard carbon microsphere morphology in the emulsion state, the present invention uses coal tar pitch as a carbon source, uses a catalyst to initiate a crosslinking reaction of other aromatic hydrocarbons in the raw material coal tar pitch, so that they form planar aromatic hydrocarbon molecules with large molecular weight, and finally form spheres under the action of surface tension, and at the same time selects a proton-type co-catalyst as a solvent to provide a cation source, improve the catalytic activity of the catalyst, and finally prepare hard carbon microspheres with a large carbon layer spacing and abundant defect sites. The preparation method is simple, economical, and environmentally friendly.

[0006] Based on the above technical effects, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing hard carbon microspheres by utilizing solvent thermal catalytic cross-linking of coal tar, comprising the following steps: adding coal tar to a solvent containing a catalyst and subjecting it to heat treatment to obtain a precursor material, and carbonizing the precursor material to obtain coal tar-based hard carbon microspheres; the catalyst is one or a combination of p-toluenesulfonic acid (C7H8O3S), aluminum chloride (AlCl3), and potassium bisulfate (KHSO4).

[0007] The above preparation method also has the following preferred implementation modes: The coal tar pitch preferably uses a low softening point asphalt, and the softening temperature is preferably in the range of 80-90°C; feasible sources include lignite, bituminous coal or anthracite, which are the dry distillation products of the above coals. Preferably, the above coal tar pitch needs to be pretreated to remove ash and minerals before adding to the reaction. The present invention provides a pretreatment implementation method as follows: coal tar pitch is mixed with anhydrous ethanol for wet ball milling, mixed acid is added to the ball milled product, and the solid product is separated and dried for standby use after the reaction is completed; further, the mixed acid is obtained by mixing hydrofluoric acid (HF) and hydrochloric acid (HCl) in a mass ratio of 1:2-4.

[0008] The catalyst is preferably one of p-toluenesulfonic acid, aluminum chloride and potassium hydrogen sulfate, and the mass ratio of the above coal tar pitch to the catalyst is 1 g: 0.1-0.5 g; the catalyst is more preferably p-toluenesulfonic acid.

[0009] The solvent is selected from anhydrous ethanol, water, anhydrous acetic acid or other carboxylic acids, wherein the water is deionized water.

[0010] The selection factor of the above catalysts is to utilize the H released by the acidic catalyst during the reaction. +The positive carbon ions are added to the aromatic rings to form positive carbon ions, which initiate cross-linking reactions with other aromatic hydrocarbons in the raw asphalt, and eventually form planar aromatic hydrocarbon molecules with large molecular weights. These planar aromatic hydrocarbons with large molecular weights aggregate and precipitate from the liquid matrix through electronic force interactions, and eventually form spheres under the action of surface tension. In order to enable the catalyst to better exert its catalytic effect, the above-mentioned solvent is preferably an organic solvent. It has been verified by the present invention that proton-based co-catalysts as solvents can provide a cation source to enhance the catalytic activity of the catalyst. Therefore, the use of anhydrous ethanol as a solvent can maximize the catalytic effect of p-toluenesulfonic acid.

[0011] The heat treatment method is as follows: add coal tar pitch to a solvent containing a catalyst, continue stirring for 10 to 14 hours, keep the reaction system at 180 to 220° C. for 10 to 14 hours, then separate the black solid product and dry it at 55 to 65° C. for 10 to 14 hours to obtain the precursor material.

[0012] The carbonization step is as follows: placing the precursor material in an inert gas atmosphere, heating it to 900-1200°C at a rate of 3-10°C / min, and keeping the temperature for reaction for 1-4 hours; the inert gas is one of argon, nitrogen, and hydrogen-argon mixed gas, including but not limited to.

[0013] The second aspect of the present invention provides coal tar pitch-based hard carbon microspheres prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides a negative electrode for a sodium ion battery, wherein the negative electrode uses the coal tar pitch-based hard carbon microspheres described in the second aspect as an active material.

[0015] The preparation method of the negative electrode of the sodium ion battery comprises the following steps: mixing the coal tar pitch-based hard carbon microspheres, the conductive agent and the binder according to the second aspect in a mass ratio of 8:0.5~1.5:0.5~1.5, and then adding a solvent to mix to obtain a black viscous slurry; coating the slurry on a metal foil, and stamping it after drying to obtain the battery negative electrode.

[0016] The conductive agent is selected from acetylene black, carbon black, carbon nanotubes, conductive graphite, graphene, Ketjen black or Super P, and the binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyvinyl alcohol (PVA), sodium alginate (Alg), β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132) or polytetrafluoroethylene (PTFE); the solvent is 1-methyl-2-pyrrolidone. In one embodiment verified by the present invention, the coal pitch-based hard carbon microspheres, acetylene black and PVDF are mixed in a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone is added to stir the mixed powder into a black viscous slurry.

[0017] The metal foil is copper foil or aluminum foil, preferably copper foil, on which the black viscous slurry is coated and dried at 55-65°C by heat radiation for about 5-7 hours. After it is completely dried, it is punched to obtain a negative electrode sheet.

[0018] According to a fourth aspect of the present invention, a sodium ion battery is provided, wherein the sodium ion battery has the battery negative electrode described in the third aspect.

[0019] The positive electrode of the above-mentioned sodium ion battery is a compound that can ionize sodium ions, and the selectable types include oxides, polyanions (such as phosphates, pyrophosphates, fluorosulfates, oxychlorides), Na superion conductors or organic compounds.

[0020] The diaphragm of the above-mentioned sodium ion battery is a polymer diaphragm, including a polyolefin composite diaphragm, a glass fiber filter paper type diaphragm, an organic polymer non-woven fabric type diaphragm, etc. In one embodiment verified by the present invention, the diaphragm is a glass fiber filter paper type diaphragm.

[0021] The sodium salt in the electrolyte of the above-mentioned sodium ion battery is sodium hexafluorophosphate (NaPF6), sodium trifluoromethanesulfonate (NaCF3SO3) or sodium bis(fluorosulfonyl)imide (NaFSI).

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a method for preparing hard carbon microspheres by using solvent thermal catalytic cross-linking of coal tar pitch, using low softening point coal tar pitch as a carbon source, using a catalyst to initiate a cross-linking reaction of other aromatic hydrocarbons in the raw material coal tar pitch, so that they form planar aromatic hydrocarbon molecules with large molecular weight, and finally form spheres under the action of surface tension. At the same time, the solvent generates steam during the reaction process, thereby forming nanopores between the cross-linked matrix, and finally preparing hard carbon microspheres with large carbon layer spacing and abundant defect sites. The preparation method is simple, economical and environmentally friendly.

[0023] 2. The present invention utilizes solvent thermal catalytic cross-linking of coal tar to prepare hard carbon microspheres. The catalyst triggers the cross-linking reaction of the matrix to form large molecular planar aromatic hydrocarbons into spheres. At the same time, the spherical structure is stabilized during the carbonization process, providing a higher tap density, so that it has a higher specific capacity when used in the negative electrode of a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0025] Figure 1 XRD patterns of the coal tar pitch-based hard carbon microspheres prepared in Example 1 and the coal tar pitch-based carbon material prepared in Comparative Example 1; Figure 2 The SEM images of the coal tar pitch-based hard carbon microspheres prepared in Example 1 and the coal tar pitch-based carbon material prepared in Comparative Example 1; in, Figure 2 a is a low-magnification SEM image of coal tar-based carbon material; Figure 2 b is a high-magnification SEM image of coal-tar-based carbon materials; Figure 2 c is a low-magnification SEM image of coal-tar-based hard carbon microsphere material; Figure 2 d is a high-magnification SEM image of coal tar-based hard carbon microsphere material.

[0026] Figure 3 The charge and discharge curves of the sodium ion batteries prepared in Example 1, Example 3 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0029] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0030] The coal tar powder in the following examples was sourced from Handan Yanjin Trading Co., Ltd., and its softening temperature was ≈80 °C.

[0031] Example 1 In this embodiment, a coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided, wherein the preparation method of the coal tar pitch-based hard carbon microsphere comprises the following steps: (1) Coal tar pitch pretreatment: Coal tar pitch powder is mixed with anhydrous ethanol and ball-milled, and then ash and minerals are removed by mixed acid (HF:HCl=1:3), centrifuged, and dried for later use; (2) Preparation of coal tar-based hard carbon microspheres: Take 0.5 g of the coal tar powder treated in step (1), add it to 35 mL of anhydrous ethanol mixed solution containing 30 wt.% p-toluenesulfonic acid and transfer it to a 50 ml polytetrafluoroethylene liner, and stir it magnetically for 12 h. Then keep it warm at 200 °C in a forced air drying oven for 12 h. Naturally cool to room temperature, vacuum filter to obtain the black powder in the suspension, and dry it in a vacuum drying oven at 60 °C for 12 h to obtain the precursor material. Subsequently, the precursor material was dried at 1000 °C for 2 min. ‒1 The heating rate was 200 °C and annealed in an Ar atmosphere for 2 h to obtain coal tar pitch based hard carbon microspheres. The coal tar pitch used was derived from anthracite.

[0032] Correspondingly, the preparation method of the sodium ion battery is as follows: S1. Grind the coal tar-based hard carbon microspheres, acetylene black and binder PVDF in a mortar at a mass ratio of 8:1:1, then add 1-methyl-2-pyrrolidone to stir the ground powder into a black viscous slurry for later use; S2. Use a 100 μm scraper to evenly coat the slurry obtained in step (1) on a copper foil, then dry the copper foil at 60° C. for 6 h, and finally punch it into a circular electrode sheet with a diameter of 12 mm. The electrode sheet is the negative electrode of the sodium ion battery; S3. Use the electrode sheet obtained in S2 as the negative electrode, sodium metal as the positive electrode, glass fiber as the separator, 1M NaPF6 as the electrolyte, and the voltage range of 0.01~3 V to prepare a sodium ion battery.

[0033] Comparative Example 1 In this embodiment, another coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided. In the preparation of the coal tar pitch-based hard carbon microsphere, the difference from Example 1 is that the operation of step (2) is as follows: 0.5 g of the coal tar pitch powder treated in step (1) is taken, 35 mL of anhydrous ethanol containing 0 wt.% p-toluenesulfonic acid is added, and the mixture is transferred to a 50 mL polytetrafluoroethylene liner and magnetically stirred for 12 h. The other settings are the same as those in Example 1.

[0034] Correspondingly, the sodium ion battery uses the coal tar pitch-based hard carbon microspheres prepared in this example as raw materials, and the other preparation methods are the same as those in Example 1.

[0035] Example 2 In this embodiment, another coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided, wherein the preparation method of the coal tar pitch-based hard carbon microsphere comprises the following steps: (1) Coal tar powder pretreatment: same as in Example 1; (2) Preparation of coal tar-based hard carbon microspheres: Take 0.5 g of the coal tar powder treated in step (1), add it to 35 mL of anhydrous acetic acid mixed solution containing 30 wt.% p-toluenesulfonic acid and transfer it to a 50 ml polytetrafluoroethylene liner, and stir it magnetically for 12 h. Then keep it warm at 180 °C in a forced air drying oven for 12 h. Naturally cool to room temperature, vacuum filter to obtain the black powder in the suspension, and dry it in a vacuum drying oven at 55 °C for 14 h to obtain the precursor material. Subsequently, the precursor material was dried at 900 °C for 3 °min. ‒1 The heating rate was 1.33°, and the mixture was annealed in an Ar atmosphere for 4 h to obtain coal tar pitch based hard carbon microspheres. The coal tar pitch used was derived from anthracite.

[0036] Correspondingly, the preparation method of the sodium ion battery is as follows: S1. Grind the coal tar-based hard carbon microspheres, acetylene black and binder PVDF in a mortar at a mass ratio of 8:0.5:0.5, then add 1-methyl-2-pyrrolidone to stir the ground powder into a black viscous slurry for later use; S2, using a 100 μm scraper to evenly coat the slurry obtained in step (1) on a copper foil, then drying the copper foil at 55° C. for 7 h, and finally punching it into a circular electrode sheet with a diameter of 12 mm, which is the negative electrode of the sodium ion battery; S3. Use the electrode sheet obtained in S2 as the negative electrode, sodium metal as the positive electrode, glass fiber as the separator, 1M NaPF6 as the electrolyte, and the voltage range of 0.01~3 V to prepare a sodium ion battery.

[0037] Example 3 In this embodiment, another coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided, wherein the preparation method of the coal tar pitch-based hard carbon microsphere comprises the following steps: (1) Coal tar powder pretreatment: same as in Example 1; (2) Preparation of coal tar-based hard carbon microspheres: Take 0.5 g of the coal tar powder treated in step (1), add it to 35 mL of anhydrous ethanol mixed solution containing 10 wt.% p-toluenesulfonic acid and transfer it to a 50 ml polytetrafluoroethylene liner, and stir it magnetically for 14 hours. Then keep it warm at 220°C in a forced air drying oven for 10 hours. Naturally cool to room temperature, vacuum filter to obtain the black powder in the suspension, and dry it in a vacuum drying oven at 65°C for 10 hours to obtain the precursor material. Subsequently, the precursor material was dried at 1200°C for 8°min. ‒1 The heating rate was 1.50°, and the mixture was annealed in an Ar atmosphere for 1.5 h to obtain coal tar pitch based hard carbon microspheres. The coal tar pitch used was derived from lignite.

[0038] Correspondingly, the preparation method of the sodium ion battery is as follows: S1. Grind the coal tar-based hard carbon microspheres, acetylene black and binder PVDF in a mortar at a mass ratio of 8:1.5:1.5, then add 1-methyl-2-pyrrolidone to stir the ground powder into a black viscous slurry for later use; S2, using a 100 μm scraper to evenly coat the slurry obtained in step (1) on a copper foil, then drying the copper foil at 65° C. for 5 h, and finally punching it into a circular electrode sheet with a diameter of 12 mm, which is the negative electrode of the sodium ion battery; S3. Use the electrode sheet obtained in S2 as the negative electrode, sodium metal as the positive electrode, glass fiber as the separator, 1M NaPF6 as the electrolyte, and the voltage range of 0.01~3 V to prepare a sodium ion battery.

[0039] Example 4 In this embodiment, another coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided. In the preparation of coal tar pitch-based hard carbon microspheres, the difference from Example 1 is that step (2) is performed as follows: 0.5 g of the coal tar pitch powder treated in step (1) is added to 35 mL of anhydrous ethanol mixed solution containing 30 wt.% aluminum chloride and transferred to a 50 mL polytetrafluoroethylene liner, and magnetically stirred for 12 h. Other settings are the same as in Example 1.

[0040] Example 5 In this embodiment, another coal tar pitch-based hard carbon microsphere and a corresponding sodium ion battery are provided. In the preparation of coal tar pitch-based hard carbon microspheres, the difference from Example 1 is that step (2) is performed as follows: 0.5 g of the coal tar pitch powder treated in step (1) is added to 35 mL of anhydrous ethanol mixed solution containing 30 wt.% potassium hydrogen sulfate and transferred to a 50 mL polytetrafluoroethylene liner, and magnetically stirred for 12 h. Other settings are the same as in Example 1.

[0041] Performance Testing Figure 1 The XRD patterns of the coal tar-based hard carbon microspheres prepared in Example 1 and the coal tar-based carbon material prepared in Comparative Example 1 show that the XRD spectrum of the coal tar-based hard carbon microspheres has two broad diffraction peaks at 25° and 43°, which are typical diffraction peaks of the hard carbon in the microspheres in the (002) and (100) crystal planes.

[0042] Figure 2 The SEM images of the coal tar pitch-based hard carbon microspheres prepared in Example 1 and the coal tar pitch-based carbon material prepared in Comparative Example 1 are shown in Figure 1. The present invention explores the effect of the catalyst on the ball formation of the hard carbon microspheres by changing the amount of catalyst added. Figure 2 As shown in Fig. 2a and Fig. 2b, it can be seen that the coal tar pitch-based carbon material without the addition of catalyst has small balls, most of which are stuck together. At the same time, there are a large number of irregular balls and larger irregular particles, and the ball formation rate is low. Figure 2 c, 2d) clearly formed a hard carbon microsphere structure, which is mainly due to the use of catalysts to initiate cross-linking reactions of other aromatic hydrocarbons in the raw coal tar pitch, forming large molecular weight planar aromatic molecules, which eventually formed spheres under the action of surface tension. This shows that the catalyst plays an indispensable role in the sphering process.

[0043] The electrochemical performance test was carried out in the voltage range of 0.01-3V. Figure 3 The figures are the charge and discharge curves of the first cycle of the batteries prepared in Example 1, Example 3 and Comparative Example 1 at 0.1 A / g. The results show that compared with the coal tar-based carbon material (Comparative Example 1) and the coal tar-based hard carbon microspheres with different catalyst addition amounts (Example 1 and Example 3), the coal tar-based hard carbon microspheres prepared in Example 1 have a significant capacity improvement for sodium ion batteries, and the first efficiency reaches ~ 90%.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing hard carbon microspheres by solvent thermal catalytic cross-linking of coal tar pitch, characterized in that: The method comprises the following steps: adding coal tar pitch into a solvent containing a catalyst and performing heat treatment to obtain a precursor material, and carbonizing the precursor material to obtain coal tar pitch-based hard carbon microspheres; The catalyst is one of C7H8O3S, AlCl3, and KHSO4, and the mass ratio of the coal tar pitch to the catalyst is 1 g: 0.1-0.5 g; The heat treatment method is as follows: add coal tar pitch to a solvent containing a catalyst, continue stirring for 10 to 14 hours, keep the reaction system at 180 to 220° C. for 10 to 14 hours, then separate the black solid product and dry it at 55 to 65° C. for 10 to 14 hours to obtain the precursor material.

2. The method for preparing hard carbon microspheres by solvent thermal catalytic cross-linking of coal tar pitch as claimed in claim 1, characterized in that: The coal tar pitch is a dry distillation product of lignite, bituminous coal or anthracite.

3. The method for preparing hard carbon microspheres by solvent thermal catalytic cross-linking of coal tar pitch as claimed in claim 2, characterized in that: The coal tar pitch needs to be pre-treated before being added to the reaction: the coal tar pitch is mixed with anhydrous ethanol and wet ball-milled, a mixed acid is added to the ball-milled product, and after the reaction is completed, the solid product is separated and dried for later use.

4. The method for preparing hard carbon microspheres by using solvent thermal catalytic cross-linking of coal tar pitch as claimed in claim 1, characterized in that: The solvent is selected from anhydrous ethanol and anhydrous acetic acid.

5. The method for preparing hard carbon microspheres by solvent thermal catalytic cross-linking of coal tar pitch as claimed in claim 1, characterized in that: The carbonization step is as follows: placing the precursor material in an inert gas atmosphere, heating it to 900-1200°C at a rate of 3-10°C / min, and keeping the temperature for reaction for 1-4 hours; the inert gas is selected from one of argon, nitrogen, and a hydrogen-argon mixture.

6. Coal-tar-based hard carbon microspheres prepared by the method according to any one of claims 1 to 5.

7. A sodium ion battery negative electrode, characterized in that: The negative electrode uses the coal pitch-based hard carbon microspheres as claimed in claim 6 as active material; The method for preparing the negative electrode of the sodium ion battery comprises the following steps: mixing the coal tar pitch-based hard carbon microspheres, the conductive agent and the binder according to claim 6 in a mass ratio of 8:0.5~1.5:0.5~1.5, and then adding a solvent to mix to obtain a black viscous slurry; coating the slurry on a metal foil, and stamping it after drying to obtain the battery negative electrode.

8. The sodium ion battery negative electrode according to claim 7, characterized in that The conductive agent is selected from acetylene black, carbon black, carbon nanotubes, conductive graphite, graphene, Ketjen black or Super P; the binder is selected from PVDF, CMC, PVP, PMMA, PAN, PAA, PVA, Alg, β-CDp, polypropylene emulsion LA132 or PTFE; the solvent is 1-methyl-2-pyrrolidone; The metal foil is a copper foil or an aluminum foil, the slurry is coated on the metal foil, dried at 55-65° C. for 5-7 hours, and then punched to obtain a negative electrode sheet.

9. A sodium ion battery, characterized in that: The sodium ion battery has the sodium ion battery negative electrode according to claim 7 or 8.

10. The sodium ion battery according to claim 9, characterized in that: The positive electrode of the sodium ion battery is a compound that can ionize sodium ions, selected from metal oxides, polyanions, Na superion conductors or organic compounds; The separator of the sodium ion battery is a polymer separator selected from a polyolefin composite separator, a glass fiber filter paper separator or an organic polymer non-woven separator; The sodium salt in the electrolyte of the sodium ion battery is NaPF6, NaCF3SO3 or NaFSI.

Citation Information

Patent Citations

  • Preparation method and application of asphalt-based carbon microspheres

    CN113562721A

  • Hard carbon material, preparation method thereof, electrode, battery and application

    CN114368739A

  • Method for preparing mesophase pitch by catalysis of promoter-Lewis acid system

    CN115521802A

  • Asphalt-based spherical hard carbon negative electrode material and preparation method and application thereof

    CN119050351A

  • Hard carbon negative electrode material and preparation method therefor, mixed negative electrode material, and secondary battery

    WO2024108771A1

Cited By

  • Asphalt-based hard carbon negative electrode material for sodium-ion battery and preparation method of asphalt-based hard carbon negative electrode material

    CN120081362A